Language, Discourse and Social Psychology
XVII, 309 p.
Keywords: Language and communication are central features of social behaviour. So, it is somewhat surprising that the social psychological study of this area has a relatively short history. In this book a leading group of scholars overview the history, theories and methods of the field, and showcase the latest developments in cutting-edge empirical work.